Power relations in higher education classes of nontraditional-age adults: Issues of gender, race and class - Elizabeth J. Tisdell (Adult Education Research Conference, 1993)
This qualitative comparative case study examined how power relationships predominantly based on gender but including race, class, and age were manifested in higher education classrooms of nontraditional-age adult students.